2011
DOI: 10.1021/jo200424q
|View full text |Cite
|
Sign up to set email alerts
|

Pyrrolo[3,2-e][1,4]diazepin-2-one Synthesis: A Head-to-Head Comparison of Soluble versus Insoluble Supports

Abstract: Aryldiazepin-2-ones are known as "privileged structures", because they bind to multiple receptor types with high affinity. Toward the development of a novel class of aryldiazepin-2-one scaffolds, the synthesis of pyrrolo[3,2-e][1,4]diazepin-2-ones on a support was explored starting from N-(PhF)-4-hydroxyproline and featuring an acid-catalyzed Pictet-Spengler reaction to form the diazepine ring. Three supports [Wang resin, tetraarylphosphonium (TAP) soluble support, and Merrifield resin] were examined in the sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 78 publications
0
21
0
Order By: Relevance
“…[15,16] In the case of thiophene, degradation was observed with a Brønsted acid, such as TFA (Table 1, Entry 12), or with a Lewis acid, such as TiCl 4 ( Table 1, Entry 13). Indeed, Lubell et al reported that TFA was able to catalyse the Pictet-Spengler cyclization reaction on the pyrrole.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[15,16] In the case of thiophene, degradation was observed with a Brønsted acid, such as TFA (Table 1, Entry 12), or with a Lewis acid, such as TiCl 4 ( Table 1, Entry 13). Indeed, Lubell et al reported that TFA was able to catalyse the Pictet-Spengler cyclization reaction on the pyrrole.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, Lubell et al reported that TFA was able to catalyse the Pictet-Spengler cyclization reaction on the pyrrole. [15,16] In the case of thiophene, degradation was observed with a Brønsted acid, such as TFA ( Table 1, Entry 12), or with a Lewis acid, such as TiCl 4 ( Table 1, Entry 13). Therefore, uncatalysed conditions in anhydrous toluene at 110°C were selected to perform all the Pictet-Spengler reactions described in this report.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the field of research concerning dihydrobenzo[e] [1,4]diazepin-2-one heterocyclic analogues, an interesting strategy for the preparation of compounds with a differential modulation of urotensin II receptor-mediated vasoconstriction was recently introduced by Lubell [32,33]. As the key intermediate, resin-bound 65 was synthesized from immobilized 4-hydroxyproline.…”
Section: [13]diazepinesmentioning
confidence: 99%